Dampak Digitalisasi Terhadap Pengelolaan Statistik Administrasi: Tinjauan Literatur - Mozin, Sri Yulianty; Botutihe, Mohamad Iqshal; Lawani, Zaskia Salwa; Aripin, Irmawati; Pulanding, Fatralisa; Sasmindar, Dwi (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Digitalization has changed different perspectives of regulatory insights administration, both in terms of effectiveness, exactness, and information openness. This inquire about points to analyze the affect of digitalization on the administration of regulatory measurements by highlighting changes within the handle of information collection, preparing, and utilization. The strategy utilized in this inquire about is writing ponder and auxiliary information investigation from different significant sources. The comes about appear that digitization increments productivity in information handling, minimizes input blunders, and quickens the dispersion of data to partners. In expansion, digitization empowers information integration over segments, in this way supporting more exact and evidence-based decision-making. Be that as it may, challenges such as information security and incongruities in get to to technology remain deterrents to the complete execution of digitization. The suggestion of these discoveries is the got to fortify computerized framework, increment human asset capacity, and arrangements that bolster advanced change within the administration of authoritative measurements.